Conservação de invertebrados em áreas urbanas: um estudo de caso com formigas no Cerrado brasileiro - Nascimento, Renata Pacheco do (2005)
One of the major threats to conservation of biological diversity is the growth and expansion of the human population, through increased exploration of natural resources and modifications in land use of natural ecosystems. One conservation strategy in urban landscapes is the creation and maintenance of public squares and parks by providing a less disturbed environment. However, few studies have focused on the ecology of ant communities in these areas. Therefore, it was evaluated the value of public squares and parks for the conservation of ants inside an urban landscape. The work was carried in the city of Uberlândia (MG), in twelve public squares, two urban parks and in three natural reserves. The size of each site, amount of pavementation, tree cover, public visitation rates, and distance to the urban center were measured. For the collection of ground-dwelling ants, pitfall traps containing sardine as attractive, were used. The traps remained in operation for 48 hours, after which the collected ants were identified. Public squares, parks and reserves differend in relation to all environmental variables measured, and there was a significant and strong correlation between these variables. In total, there were 3.125 species records and 142 species. The average richness of species per transect was greater in the reserves than in the others three habitats, and greater in the parks and public squares in residential areas than public squares in the city center. The species accumulation curve for public squares in the city center indicates that the majority of the species from this site were captured with the sampling effort employed in this study. There was a negative relationship between the abundance of exotic ant species and ant species richness, a pattern, mostly caused by the presence of Pheidole megacephala. There was no exotic species in the parks and reserves. Area and distance to the urban center showed a positive relationship with ant species richness. There was also a difference in the composition of species between the more preserved areas (parks and reserves) and the public squares. Some species presented strong association with a given type of habitat, and thus could be used as indicators of the state of conservation of the studied environments. Within the urban landscape, parks presented the greatest conservation value. However, it was found that public squares in residential areas can support a relatively high number of species, especially in larger squares and those close to natural areas. The presence of exotic Pheidole megacephala showed to be an important factor affecting species richness in the city center public-squares, suggesting that ant communities in these sites are structured by inter-specific competition rather by environmental factors. The results of this study indicate that some ants species, such as Pheidole megacephala and Cardiocondyla wroughtonii, can be considered as indicators of urban vegetated areas, and thus could be used as bioindicators of the conservation potential oh this areas.